(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article, based on ethnographic field materials and sources, examines the child-rearing system in traditional Kyrgyz families for children aged 3 to 7 years. This system of upbringing, based on centuries-old traditions and values, has been passed down from generation to generation. The early childhood period is considered extremely important for the development of fundamental skills, as well as personal and social behavior. The child-rearing system in Kyrgyz families is closely linked to the peculiarities of ethnic life, ethnic-social norms, and the family and community way of life. The fruits of collective creativity of generations, the accumulated experience of traditional child-rearing, include methods of shaping the child’s personality and adapting them to life in a particular society. The methods of upbringing and socialization of the younger generation are as new as human life itself, yet as old as human civilization. Regardless of the achievements in culture and science, upbringing has been and remains an eternal system: new generations absorb and adapt to the world around them, and this process continues as they integrate into society, becoming part of that world and community.